MITIGASI KEDIP TEGANGAN AKIBAT BEBAN TANUR BUSUR LISTRIK MELALUI KOMPENSATOR SERI: STUDI KASUS PT. KRAKATAU STEEL - Muliaty Yantahin (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The goal of this research project is to show how the series capacitor compensator can reduce the effects of voltage-dip problem in an electrical arc furnace operation. The case of PT. Krakatau Steel (a major steel company in Indonesia) is taken into consideration. A 195 KVA/220 arc furnace operating in the company is known to cause votage-dip problem in the surrounding distribution system supplied by a 400 MW electrical power plant. The dip is recorded as ranging from 8% to 17%.